Stimulatory effects of human cytomegalovirus tegument protein pp71 lead to increased expression of CCL2 (monocyte chemotactic protein-1) during infection - Naing, Zin; Webel, Rike; Hamilton, Stuart; Schmeiser, Cathrin; Scott, Gillian; Marschall, Manfred; Rawlinson, William (Journal of General Virology, 2015)
Human cytomegalovirus (CMV) is the most common infectious cause of congenital birth defects in developed countries. Studies of infected amniotic fluid and placentae show CMV infection leads to a pro-inflammatory shift in cytokine profiles with implications for pathogenesis of foetal disease. ELISA, immunofluorescence and real-time-PCR assays were used to investigate CCL2 (monocyte chemotactic protein-1) and TNF-? changes following CMV infection of human fibroblasts, as well as following transient expression of CMV gene products in HeLa cells. Infection of human fibroblasts with CMV AD169 resulted in increased cytoplasmic and extracellular expression of CCL2 during early stages of infection, followed by marked downregulation of the chemokine at late times. Induction of CCL2 was not observed with CMV clinical strain Merlin, consistent with the postulated immune-evasion potential of this genetically intact WT strain. Comparison between live and UV-irradiated virus infections showed that changes in CCL2 levels were a direct response to active CMV replication. There were no significant changes in TNF-? expression during a parallel time-course of CMV infection. In transient transfection assays, overexpression of CMV tegument protein pp71 resulted in intracellular and extracellular upregulation of CCL2 protein. mRNA analysis showed that pp71-induced elevation in CCL2 was mediated through transcriptional upregulation. The data showed that CMV-induced upregulation of CCL2 during early stages of infection was mediated, at least in part, by stimulation of viral pp71, which may contribute to viral pathogenesis through enhanced virus dissemination.
EVALuna2:8267